Outcomes and Frequency of Neonatal Diseases Observed in the Neonatal ICU of the Paediatric Department of a Tertiary Care Hospital - Amanullah Memon, Naheed Haroon Kazi, Safiya Javed, Naseem Begum, Loveena, Huma Qureshi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The present study aims at assessing the frequency of diseases in neonates that have to be admitted to the neonatal intensive care unit and the outcomes of those diseases Study design: A cross-sectional study Place and Duration: This study was conducted at Kulsumbai Valika Social Security Site Hospital Karachi from November 2021 to November 2022. Methodology: All the neonates that presented to NICU (Neonatal Intensive Care Unit), were included in the study. Demographic data related to all the patients were collected, such as gestational age, gender, weight at the time of admission, and date of admission. Clinical data that was collected included diagnosis at the time of admission, final diagnosis, referral, mortality within four weeks of the total life of the patient, and discharge date. The mode of admission, either in outpatient or emergency, was also noted. Results: A total of 210 patients were added to the present study. Overall 90 (42.86%) patients were admitted in the first six hours of life. The main reason for admission was neonatal sepsis in 57 (27.14%) patients. Other reasons included prematurity in 52 (24.76%) patients, neonatal jaundice in 25 (11.9%) patients, birth asphyxia in 15 (7.14%) patients, IUGR (intrauterine growth restriction) in 14 (6.66%) patients, respiratory distress syndrome in 11 (5.23%), meconium aspiration syndrome in 12 (5.7%) patients, and the remaining 24 patients had other health issues. A total of 182 (86.67%) patients were discharged from the hospital in stable condition, while 8 (3.8%) were referred to a more advanced healthcare facility. Overall 11 (5.2%) patients died in the hospital and 9 (4.28%) left against medical advice (LAMA). Conclusion: Prematurity and neonatal sepsis are the main causes of neonatal admissions in Neonatal ICU. These causes are followed by Birth Asphyxia and Neonatal Jaundice. Keywords: Neonate, Neonatal ICU, Admission, Birth Asphyxia, Neonatal Sepsis, Prematurity, Neonatal jaundice